Letter to Rita Dobson from Jane Tolmach - Jane Tolmach:::::: (1976)
In a May 18, 1976 letter, Jane Tolmach thanked Rita Dobson and the California Federation of Business and Professional Women's Clubs for their endorsement and financial contribution to her Assembly campaign. She noted that the BPW contribution was the largest she had received and described it as both exciting and timely. Tolmach reported that her campaign was progressing well but emphasized the high costs of mailings, brochures, and advertising before the June 8 primary. She praised BPW for actively supporting the election of women to office. She concluded by affirming her intention to be a strong advocate for women's concerns in Sacramento.